Scale-Dependent Effects of Plant Diversity Drivers Across Different Grassland Habitats in Ukraine - Buzhdygan, Oksana; Baldauf, Selina; Borovyk, Dariia; Vynokurov, Denys; Ladouceur, Emma; Chusova, Olha; Iemelianova, Svitlana; Budzhak, Vasyl; Tietjen, Britta; Bezrodnova, Olga; Bezsmertna, Olesya; Chorney, Illya; et al. (Ecology and evolution, 2025)
Understanding the factors governing grassland biodiversity across different spatial scales is crucial for effective conservation and management. However, most studies focus on single grain sizes, leaving the scale-dependent mechanisms of biodiversity drivers unclear. We investigated how climate, soil properties, abiotic disturbance, and land use influence plant diversity across two fine spatial scales in various grassland types in Ukraine. Using spatially explicit data on plant species presence and their cover, collected at smaller (10 m2) and larger (100 m2) grain sizes, we assessed spatial β-diversity-the variability of biodiversity between scales. We analyzed whether the effects of ecological drivers on β-diversity are mediated by changes in species evenness, density (total cover), and intraspecific aggregation in plant community. In our study, the most influential factors of local plant diversity at both grain sizes were climate variables, followed by soil humus content, litter cover, and soil pH. Soil and litter effects were primarily driven by the response of locally rare species, while climate and grazing effects were driven by locally common species. The strength of most of these effects varied between spatial scales, affecting β-diversity. Soil properties influenced β-diversity through changes in total plant community cover, while the effects of climate and litter operated via changes in species evenness and aggregation. Our findings highlight that biodiversity responses to climate, soil factors, and litter depend on the size of the sampled area and reveal the role of total plant cover, evenness, and aggregation in driving fine-scale β-diversity in grasslands across different habitat types.
Keywords: scale‐dependency; β‐diversity; grasslands; biodiversity drivers; biodiversity; fine spatial scale